Strategi Komunikasi Pemasaran Digital dalam Membangun Customer Trust @Ricellystore Via Instagram - Muhammad Ilyas; Niyu Niyu; Herman Purba (STARKI, 2023)
Apart from being used to socialize, Instagram social media is also used as a medium for promotions, buying and selling transactions. The occurrence of various frauds in online transactions sets a precedent that can be detrimental to these online business actors. In online transactions, building trust is an important step that must be taken by business actors, especially for business actors who are just starting their business. @Ricellystore is a new online business actor engaged in the used gadget sector, but they are able to build trust in a relatively short time with sales figures increasing significantly every month. This study aims to find out how the digital marketing communication strategy carried out by @Ricellystore on Instagram builds customer trust. This study uses a descriptive qualitative approach, where data is obtained through interviews, observation, and documentation. The results of the research show that the @Ricellystore digital marketing communication strategy starts with strengthening Perceived web vendor reputation and Perceived web quality, making their store reachable and available, having added value, and maximizing unpaid promotion with the power of word of mouth (WOM) and resellers from their customers. Abstrak Selain digunakan untuk bersosialisasi saat ini media sosial Instagram juga digunakan sebagai media untuk promosi dan transaksi jual beli. Terjadinya berbagai penipuan dalam transaksi online menjadikan preseden yang dapat merugikan para pelaku usaha online tersebut. Dalam bertransaksi online membangun trust menjadi salah satu langkah penting yang harus dilakukan oleh pelaku usaha, terlebih bagi pelaku usaha yang baru merintis usahanya. @Ricellystore merupakan pelaku usaha online baru yang bergerak pada sektor gawai bekas, namun mereka mampu membangun kepercayaan dalam waktu relatif singkat dengan angka penjualan yang meningkat signifikan setiap bulannya. Penelitian ini bertujuan untuk mengetahui bagaimana strategi komunikasi pemasaran digital yang dilakukan @Ricellystore di Instagram dalam membangun customer trust. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dimana data diperoleh melalui metode wawancara, observasi, dan dokumentasi. Strategi komunikasi @Ricellystore dimulai dengan memperkuat Perceived web vendor reputation dan Perceived web quality, menjadikan toko mereka reachable and available, mempunyai adding value, dan memaksimalkan unpaid promotion dengan kekuatan word of mouth (WOM) dan reseller dari customer mereka.